The off-campus student teaching program of private teacher colleges in Davao City its organization, administration and supervision - Lozada, Enrique M. 1924- (s.n.], 1967)
This study provides a description of the existing conditions in the organization, administration, and supervision of the off-campus student teaching program of private teacher colleges in Davao City in order to identify the problems encountered in the field and to offer solutions relevant to these aspects.